Improving Critical Thinking Skills in Early Childhood through Science Activities - Suranti, Lilis; Asmawulan, Tri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Early childhood education serves as a crucial foundation for shaping children’s thinking abilities, character, and personality, which in turn determine the quality of future human resources. Critical thinking skills are essential competencies that must be nurtured from an early age so that children are able to analyze, solve problems, and make evidence-based decisions. This study aims to analyze the implementation of science activities as a medium for developing critical thinking skills in early childhood at KB Aisyiyah Pracimantoro. A qualitative approach with a case study design was used to gain an in-depth understanding of the dynamics of science learning. Data were collected through participatory observations, in-depth interviews with teachers and four children aged 4-5 years, and documentation analysis covering the learning period from May to August 2025. The findings indicate that the science activity themed "A Balloon Inflates Without Being Blown" successfully stimulated all indicators of critical thinking, including the ability to ask questions through "why" and "how," observe and analyze process details, make proportional predictions about the relationship between quantity and outcome, solve problems with perseverance, evaluate results by providing reasons, as well as communicate and argue through sequential explanations and articulation of causal understanding. This study highlights that simple inquiry-based science activities are effective strategies for developing early childhood critical thinking skills and are highly suitable for integration into sustainable early childhood education curricula.